ANALISIS PENGGUNAAN TEKNOLOGI AUGMENTED REALITY SEBAGAI PENGUATAN LITERASI DIGITAL PADA PEMBELAJARAN IPA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SD SKOW SAE - Ria Ristiani; Tiffany Shahnaz Rusli; Hidayah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research analyzes the use of Augmented Reality (AR) technology to strengthen digital literacy in natural science education and its effect on student motivation at SD Inpres Skow Sae. The research method used was Concurrent Mixed Methods, involving 32 fifth-grade students. Quantitative data were collected through a learning motivation questionnaire, and qualitative data were gathered through observation and interviews. The results showed that the use of AR had a significant and positive impact on student motivation. The average motivation score reached 87.5 out of an ideal score of 100, with 68.75% of students in the